Game-based didactic strategy for teaching basic vocabulary in english in elementary education - Jamarillo Ramírez, Jordán Javier; Vera Valdiviezo, Lilibeth Susana (Machala : Universidad Técnica de Machala, 2021)
The main purpose of this research is to improve the teaching of basic English vocabulary in elementary general education students through the use of games as a didactic method, since, the teaching process is constantly changing due to the needs that arise, there is still a lack of didactic strategies, and therefore, through games, the aim is to improve this educational practice. The research responds to a qualitative paradigm, with an action-research design, making use of theoretical methods that allowed systematizing different existing criteria on the subject, facilitating a better approach to the work, while with the help of empirical methods such as participant observation, diagnostic test, and interview with area teacher, allowed diagnosing the initial state of the study population made up of students in the fourth year of general basic education of the "Gran Colombia" fiscomisional educational unit of the city of Alamor, leaving aside the selection of the sample. Hence, considering the existing needs of the students, a didactic strategy based on games is provided, which favors both teaching and learning in children and which was planned for a unit of study. Finally, it is suggested to continue addressing the topic using new technological tools, as well as the time determined for each activity, so that the process is active and effective.
Esta investigación tiene como fin principal mejorar la enseñanza de vocabulario básico de inglés en alumnos de educación general básica a través del empleo del juego como método didáctico, pues, aunque el proceso de enseñanza se encuentre en constante cambio debido a las necesidades que se presentan, aún se puede evidenciar carencia en las estrategias didácticas, por lo que a través del juego se pretende mejorar esta práctica educativa. La investigación responde a un paradigma cualitativo, con un diseño de investigación- acción, haciendo uso de métodos teóricos que permitieron sistematizar distintos criterios existentes sobre la temática, facilitando un mejor abordaje del trabajo, mientras que con la ayuda de los métodos empíricos como la observación participante, test de diagnóstico, y entrevista a docente de área, permitieron diagnosticar el estado inicial de la población en estudio conformado por los estudiantes de cuarto año de educación general básica de la unidad educativa fiscomisional “Gran Colombia” de la ciudad de Alamor dejando de lado la selección de la muestra. Es así que considerando las necesidades existentes en el alumnado se aporta con una estrategia didáctica basada en el juego, que favorece tanto la enseñanza como el aprendizaje en los niños y que fue planificada para una unidad de estudio. Finalmente se sugiere seguir abordando el tema haciendo uso de nuevas herramientas tecnológicas, así como el tiempo determinado para cada actividad, de tal modo que el proceso se dé activa y efectivamente.
Keywords: DIDACTIC; METHOD; TEACHING; STRATEGY